Pengembangan Modul Pembelajaran IPA Berbasis Project Based Learning pada Materi Hubungan antar Makhluk Hidup dalam Ekosistem Siswa Kelas V Sekolah Dasar - Adeng, Adeng; Anwar, Moh. Farid Nurul; Chotimah, Chusnul (Educational Consultant & Counseling Career (EC3) Mataram, 2023)
The objective of this improvement is to deliver a legitimate and effective undertaking based science learning module. The five phases of the ADDIE model — investigation, plan, advancement, execution, and assessment — make up the innovative work (Research and development) work in the direction of utilization. Three validators—material, language, and design specialists—participated in the completion of two validity phases of the development process. The experiment involved ten students from SDN 2 Tlogomas in Malang city, as well as the homeroom instructor for class V. The second stage approval results showed that media specialists scored a normal of 68.8% with respectable/great measures, language specialists scored a normal of 88% with fair/great standards, and material specialists scored 94.5% with exceptionally respectable/generally excellent rules, Without modification, the module's legitimacy and appropriateness for field preliminaries can be closed. The exceptionally commendable instructor reaction survey II got a score of 80%, while the understudy reaction poll had a typical score of 82%. The aftereffects of the educator reaction poll I were 92%. The module is very helpful for learning, it tends to be finished up.